A decade of Learning Media and Technology: Looking back and looking forward - Selwyn, N; Eynon, R; Potter, J (Taylor and Francis, 2017)
This year has seen some editorial changes for LMT. Neil’s editorial role for the journal came to an end, and John joined as co-editor of LMT. Given this context, we thought it was an appropriate moment to take stock of the journal: where we were in 2010, where we are now, and where we hope to be in 2010. Below, each of us reflects on our experiences of editing LMT, and our hopes for its future.